Figurative Language on The Lyrics Of The Song by Mili In The Game Library of Ruina - Belliawan Pramudya (JURNALISTRENDI : JURNAL LINGUISTIK, SASTRA, DAN PENDIDIKAN, 2024)
This study observes the intricate realm of figurative language contained in the song lyrics of MILI, a Japanese music group known for their ethereal and emotive compositions, specifically within the context of the game "Library of Ruina." The analysis focuses on describing the layers of metaphors, similes, personification, and other figurative elements woven into the lyrics, with the aim of elucidating the poetic and emotional dimensions that contribute to the thematic richness of the music. The methodology involves a comprehensive examination of MILI's lyrics, drawing from a curated selection within the game "Library of Ruina." Employing a qualitative approach, the study identifies and categorizes various forms of figurative language, exploring how these linguistic devices enhance the lyrical narrative and resonate with the overarching themes of the game. The analysis extends beyond linguistic elements to consider the cultural, historical, and aesthetic contexts that shape the use of figurative language in MILI's songwriting. The findings of this research are expected to uncover the nuanced ways in which MILI utilizes figurative language to evoke emotions, convey complex narratives, and contribute to the immersive experience of "Library of Ruina." By marrying elements of linguistics, musicology, and cultural studies, this study contributes to a deeper understanding of the symbiotic relationship between music and narrative, providing insights into the broader artistic significance of MILI's contributions to the gaming landscape.